PSI-1 An Evaluation of Functionality of Cryopreserved Sperm Cells Treated with Heifer-Plus™. (21st September 2022) - Ruemke, Heather R; Runyan, Cheyenne L; Waddell, Jolena N; Roper, David; Poe, A Brant; Daigneault, Brad
Abstract: The commercial beef cattle industry produces calves for replacement or slaughter. Female replacements are important to advance herd genetics, therefore, a tool to influence sex ratios may enhance reproductive efficiency. A commercial semen sexing kit, Heifer-Plus™, used in conjunction with artificial insemination, may alter the sex ratio of offspring by increasing motility of the X chromosome-bearing sperm. The aim of this research was to assess the methodology of Heifer-Plus™ through evaluation of motion patterns and kinematic parameters in conventional semen straws. Four bulls representing Angus, Wagyu, and Holstein breeds were utilized. Six straws of cryopreserved semen from each bull were thawed in a water bath (37.5°C for 35 sec). Three straws from each bull were pooled and treated with Heifer-Plus™ and 3 straws were pooled as the no-treatment control. Post treatment, all samples were aliquoted in microcentrifuge tubes and Computer Assisted Semen Analysis (CASA) measurements of motility and kinematic factors were assessed. Semen samples were held at 37.5°C for incubation for three 15-min periods (15-mins, 30-mins, and 45-mins) measuring thermoresistance and longevity of spermatozoa. After incubation, 80 µL of each semen sample were observed on CASA. Data were analyzed using ANOVA method in GraphPad Prism and P-values ≤ 0.05 were considered significant. No effect of treatment on motility parameters or rapid velocity were measured, however there was a decrease in total motility (P=0.0045), progressive motility (P=0.0115) and rapid velocity (P =0.0099) across time intervals. Heifer-Plus™ treated cells had higher incidence of static velocity compared to control (P = .0038). Semen samples were clustered into subpopulation threshold-based on sperm average path velocity (VAP) and linearity (LIN) at each time point. Spermatozoa treated with Heifer-Plus™ consistently exhibited a high velocity and variable linearity therefore were categorized consistently into two categories at each time point.